2020
DOI: 10.1029/2019ja027506
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Differences of the Northern Equatorial Ionization Anomaly Between the Eastern Asian and American Sectors

Abstract: The morphological difference of the northern equatorial ionization anomaly between the eastern Asian and American sectors is statistically studied with ground-based total electron content data from 2000 to 2011. The intensity (Ic), latitudinal location (Lc), and occurrence time (Tc) of the daytime equatorial ionization anomaly crest are derived from daytime peak total electron content in time-latitude plots. The main results are as follows. Lc in the two sectors exhibits an apparent difference, especially in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 68 publications
7
34
0
Order By: Relevance
“…These modeling results were supported by the statistical study by Liu, Zhang, Mo, et al. (2020), which revealed that the northern EIA crest in the American sector tends to approach (deviate from) the geomagnetic equator in the Northern Hemispheric winter (summer). The hemispheric asymmetry of the PSSD perturbations in the low latitude in our result is consistent with the hemispheric asymmetry in the EIA crest location evolution.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These modeling results were supported by the statistical study by Liu, Zhang, Mo, et al. (2020), which revealed that the northern EIA crest in the American sector tends to approach (deviate from) the geomagnetic equator in the Northern Hemispheric winter (summer). The hemispheric asymmetry of the PSSD perturbations in the low latitude in our result is consistent with the hemispheric asymmetry in the EIA crest location evolution.…”
Section: Discussionsupporting
confidence: 68%
“…Simulation studies provided evidence that such a northward transequatorial wind tends to induce a dual-crest structure of EIA whose northern crest is closer to the geomagnetic equator than the southern one (Abdu, 2005;Nanan et al, 2012). These modeling results were supported by the statistical study by Liu, Zhang, Mo, et al (2020), which revealed that the northern EIA crest in the American sector tends to approach (deviate from) the geomagnetic equator in the Northern Hemispheric winter (summer). The hemispheric asymmetry of the PSSD perturbations in the low latitude in our result is consistent with the hemispheric asymmetry in the EIA crest location evolution.…”
Section: The Hemispheric Asymmetry Of Perturbations In the Low Latitudementioning
confidence: 86%
“…The eastern Asia-Australia sector also has groundbased ionospheric observation network across both hemispheres with relatively good resolutions. The geomagnetic field configuration, atmospheric waves activities, and the background ionospheric features in the eastern Asia-Australia sector significantly differs from those in the American sector (Liu et al, 2020). The 2009 SSW is one of the strongest SSW events in record with quiet solar and geomagnetic activities (Manney et al, 2009;Yamazaki et al, 2020, and reference therein), which benefits the analysis of the lower-atmosphere influence to the ionosphere during the SSW.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the EIA crests derived from CHAMP measurement (the electron density data obtained from the CHAMP Planar Langmuir Probe observation) are used for comparison with that from GPS observation. Since the CHAMP satellite has the nearly circular and polar orbit at approximately 400-km altitude with inclination of 87° (Reigber et al, 2002), its trajectory will meridionally pass through the EIA crest region, and the latitude corresponding to maximum electron density value can be used to locate EIA crest (Liu et al, 2020). There are distinct difference of EIA crest between the eastern Asian and American longitudinal sectors due to the difference in the displacement between the geographical equator and dip equator (Liu et al, 2020), so the daily average EIA crest at 0-180°E every day is used to describe the variation in northern and southern EIA region.…”
Section: Methodsmentioning
confidence: 99%
“…Since the CHAMP satellite has the nearly circular and polar orbit at approximately 400-km altitude with inclination of 87° (Reigber et al, 2002), its trajectory will meridionally pass through the EIA crest region, and the latitude corresponding to maximum electron density value can be used to locate EIA crest (Liu et al, 2020). There are distinct difference of EIA crest between the eastern Asian and American longitudinal sectors due to the difference in the displacement between the geographical equator and dip equator (Liu et al, 2020), so the daily average EIA crest at 0-180°E every day is used to describe the variation in northern and southern EIA region. It should be noted that the local time of each satellite trajectory passing through the EIA crest changes day by day; the EIA crests measured by CHAMP are not the daily most developed EIA crest.…”
Section: Methodsmentioning
confidence: 99%